Detection of Zika Virus Replication in Human Semen by Reverse-Transcription Polymerase Chain Reaction Targeting of Antisense Ribonucleic Acid. (13th February 2020) - Huits, Ralph; De Smet, Birgit; Grard, Gilda; Eggermont, Kaat; Minto-Bain, Catherine; Jess, Natalie; Leparc-Goffart, Isabelle; Malvy, Denis; Cnops, Lieselotte
Abstract: Background: Persistence of Zika virus (ZIKV) ribonucleic acid (RNA) in semen is common after infection. Methods: We designed a reverse-transcription polymerase chain reaction assay that targets antisense ZIKV RNA (asRNA) to assess ZIKV replication competence in ZIKV RNA-positive semen samples. Results: We detected ZIKV asRNA in semen of 9 of 19 men (47.4%) diagnosed with ZIKV infection. All asRNA-positive samples had high ZIKV loads (cycle threshold values <26) and were obtained within 21 days of symptom onset. Conclusions: The sensitivity of the asRNA assay for detection of ZIKV replication was higher than that of conventional virus isolation methods (47.4% vs 21.1%, P = .032). Abstract : We designed an RT-PCR assay that targets antisense Zika virus RNA. In semen samples of 19 men diagnosed with Zika virus infection, the antisense RT-PCR had higher sensitivity than virus isolation for detecting the presence of replication competent virus.